Pituitary infarction: a potentially fatal cause of postoperative hyponatraemia and ocular palsy. (17th March 2011) - Prescott, Helen; Ellis, Elna; Soule, Steven
Abstract : Postsurgical hyponatraemia with ocular palsy suggests hypopituitarism from haemorrhagic infarction of an unsuspected pituitary adenoma